2013
DOI: 10.1002/app.39334
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bio‐oil and epoxidized linseed oil on physical, mechanical, and biological properties of treated wood

Abstract: In this article, the effects of bio‐oil and epoxidized linseed oil (ELO) on water absorption, tangential swelling, decay and insect resistance, thermo‐gravimetric analysis, and mechanical properties of treated wood samples were studied. The bio‐oil used in this article was by‐product of ThermoWood thermal modification process. Linseed oil and hydrogen peroxide were used to prepare ELO. The results indicated that the samples treated with bio‐oil had lower water absorption than that of the control group. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…ELO can be crosslinked as any conventional epoxy resin by using amines [23,27] and anhydrides [28,29]. In the last years some researches have focused on the use of ELO as matrix for composite materials in combination with different reinforcements [29][30][31] . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 The research reported here focuses on the development of environmentally friendly composite laminates based on epoxidized linseed oil (ELO) matrix and slate fabrics obtained from slate fibers manufactured by melt spinning from wastes.…”
Section: Introductionmentioning
confidence: 99%
“…ELO can be crosslinked as any conventional epoxy resin by using amines [23,27] and anhydrides [28,29]. In the last years some researches have focused on the use of ELO as matrix for composite materials in combination with different reinforcements [29][30][31] . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 The research reported here focuses on the development of environmentally friendly composite laminates based on epoxidized linseed oil (ELO) matrix and slate fabrics obtained from slate fibers manufactured by melt spinning from wastes.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few publications dealing with ELO for wood protection (Panov et al 2010;Terziev and Panov 2011;Temiz et al 2013). For example, Terziev and Panov (2011) reported the anti-swelling efficiency (ASE) of pinewood in the range of 50-60%, with oil retentions of only 80-120 kg m -3 .…”
Section: Introductionmentioning
confidence: 99%
“…This efficiency improvement is not enough in-ground use. Temiz et al (2013) carried out a test with larvae of the house longhorn beetle (Hylotrupes bajulus) and concluded that ELO (at 200 kg m -3 retention) could increase the growth and survival rate of larvae. Panov et al (2010) studied the hydrophobic properties of linseed oil, ELO, tall oil ester, and epoxidized tall oil esters in combination with ELO and acetic acid (AA) as catalyst mixed at a ratio of 7:3 (by wt.).…”
Section: Introductionmentioning
confidence: 99%
“…There is an opportunity to link any plant oil to the wood cell wall and accelerate polymerisation reaction by epoxidizing the oil and subsequently impregnating it in the presence of a catalyst (Treu et al 2004;Temiz et al 2007Temiz et al , 2013. Few publications on the use of epoxidised oils for wood protection were found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Few publications on the use of epoxidised oils for wood protection were found in the literature. Recently, investigations on the protective properties of ELO have been carried out (Panov et al 2010;Terziev and Panov 2011;Temiz et al 2013), and some promising results were reported. For instance, Terziev and Panov (2011) reported anti-swelling efficiency (ASE) of wood within the range of 50 to 60%, achieved with oil retention of only 80 to 120 kg/m 3 .…”
Section: Introductionmentioning
confidence: 99%